PERENCANAAN SUDETAN UNTUK PENANGGULANGAN GERUSAN TEBING DI SUNGAI LUSI - Aedo Radewa Nayapada; Suwarto Hari Sulakso; Pranoto Sapto Atmojo; Hari Nugroho (Jurnal Karya Teknik Sipil, 2015)
Flood is a condition in which the rain water runoff is not able to be streamed by a river due to water discharge flow exceeds the capacity flow over to to areas that are not as functions. The problem of flooding that occurred in the village of Kendayaan Ngawen Blora caused by Lusi River overflow. At the area meandering river channel (meander) so that when the flood discharge causes overflow and bank scouring. To overcome these problems planned for river shortcut and checkdam. Shortcut serves to divert the flow of water so it does not happen again outburst floods. While checkdam serves to reduce bank scouring due to the speed that is too high after the river shortcut design. The maximum discharge of the river with a certain return period is calculated by using the method of Melchior, FSR Java-Sumatra, Flood Marking and Passing Capacity. Obtained from the calculation of flood discharge plan (Q50) of 622 m3/s. Then proceed calculations using HEC-RAS software to determine the impact of the flood discharge plan to the cross section of the river, so that it can be seen a part of the river that needs to be repaired. Part of the river needs to be fixed is at (STA L.610-L.613) along the ± 810 m. The repair process is done by river shortcut design while maintaining the existing river channel. Flood discharge flow divider discharge shared use of the building to the proportion of 500 m3/s in shortcut and 122 m3/s on existing groove. With the second building above expected flood in the village Kendayaan can be controlled.